Working for Less? Women's Part-Time Wage Penalties across Countries - Bardasi, Elena (2012)
This paper investigates wage gaps between part- and full-time women workers in six OECD countries in the mid-1990s. Using comparable micro-data from the Luxembourg Income Study (LIS), for Canada, Germany, Italy, Sweden, the UK, and the US, the paper first assesses cross-national variation in the direction, magnitude, and composition of the part-time/full-time wage differential. Then it analyzes variations across these countries in occupational segregation between part- and full-time workers. The paper finds a part-time wage penalty among women workers in all countries, except Sweden. Other than in Sweden, occupational differences between part- and full-time workers dominate the portion of the wage gap that is explained by observed differences between the two groups of workers. Across countries, the degree of occupational segregation between female part- and full-time workers is negatively correlated with the position of part-time workers' wages in the full-time wage distribution.